TAXATION SYSTEM: A COMPARISON BETWEEN THAILAND AND THE PHILIPPINES - Pinthong, Rattana; Pajongwong, Paiboon; Svetalekth, Thamrongsak (International Journal of Engineering Technologies and Management Research, 2018)
The purpose of this research to study of taxation system, taxpayers, taxation agencies, tax rates, penalties, term and conditions of tax privileges and comparative analysis of taxation systems between Thailand and Philippines. The findings of tax system comparison were the difference of tax collection organization between Thailand and Philippines, however, both countries have the same tax system that are tax baskets, tax regulations, tax benefits. From these findings can be concluded that taxpayers or entity in Thailand has more advantage than Philippines’s in tax allowance regulations, personal tax income allowance favoured to taxpayers for lower tax rate. Moreover, the tax rate in Thailand is lower than in Philippines resulting to proprietors or investors could bring these proceeds to expand their business or investment, finally, it will generate economic growth.